Implementation of the Algorithm for Corrective and Preventive Measures in the Process of Adaptive Physical Education of Pupils with Special Needs - Svitlana Savliuk; Vitalii Kashuba; Victoria Romanova; Sergiy Afanasiev; Nataliia Goncharova; Igor Grygus; Rafal Gotowski; Ihor Vypasniak; Andrii Panchuk (OVS LLC, 2020)
Purpose. The research has developed and substantiated the algorithm for implementation of corrective and preventive measures in the process of adaptive physical education of pupils with special needs (visually impaired children with postural disorders). Materials and methods. Twenty-eight ten-year-old visually impaired children with postural impairments (scoliotic posture or round back) participated in the experiment. Theoretical analysis, synthesis and generalization of scientific literature, Internet resources, pedagogical experiment, visual posture screening (Bibyk, Kashuba, Nosova, 2012), photography, testing, methods of mathematical statistics.  Results. The developed algorithm of corrective and preventive measures corresponds to the aim, objectives, conditions, principles, forms, didactics, control measurements, and criteria of effectiveness. During the implementation of the algorithm for corrective and preventive measures in the process of adaptive physical education of visually impaired children with postural disorders in the experimental group, there was a statistically significant (p < 0.05) improvement of the indicators of the posture bio-geometric profile and physical characteristics: strength endurance at significance level p < 0.05 and vertical body strength at significance level p < 0.05 and p < 0.01.  Conclusions. The results of the researches have confirmed the effectiveness of the developed algorithm for corrective and preventive measures, namely: improvement of the posture bio-geometric profile and increase in the level of physical qualities of visually impaired children with postural disorders. Quantitative changes at the level of p <0.05 and p <0.01 of the studied indicators, harmonious development of the individuals, and successful social adaptation in communication with healthy peers prove the effectiveness of the algorithm. At the end of the transformation experiment, based on the assessment of the posture bio-geometric profile, it was determined that ten-year-old visually impaired children with a scoliotic posture or round back improved their indicators from below-average to above-average level; strength endurance indicators from basic to intermediate and sufficient level of motor readiness; static equilibrium indicators from basic and low to medium and above-average level.